A Pain in the Backside: A Case Report of Coxa Saltans Occurring at the Proximal Hamstring Origin. Issue 3 (May 2014) - Shur, Natalie; Dandachli, Wael; Findlay, Iain; Beech, Zine; Bankes, Marcus J. K.
Coxa saltans occurring at the proximal hamstring origin has been rarely reported in the literature. It is better known as occurring at the iliotibial band or the iliopsoas tendon. We report a case of coxa saltans due to subluxation of the origin of the long head of biceps femoris tendon at the ischial tuberosity. This was successfully treated using a mini-open surgical technique. Six weeks postoperatively, the snapping and the associated pain were abolished and the patient was able to resume their participation in athletic activities.